2020
DOI: 10.1007/jhep03(2020)046
|View full text |Cite
|
Sign up to set email alerts
|

A supersymmetric theory of baryogenesis and sterile sneutrino dark matter from B mesons

Abstract: Low-scale baryogenesis and dark matter generation can occur via the production of neutral B mesons at MeV temperatures in the early Universe, which undergo CP-violating oscillations and subsequently decay into a dark sector. In this work, we discuss the consequences of realizing this mechanism in a supersymmetric model with an unbroken U (1) R symmetry which is identified with baryon number. B mesons decay into a dark sector through a baryon number conserving operator mediated by TeV scale squarks and a GeV sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 101 publications
(289 reference statements)
0
36
0
Order By: Relevance
“…[66,67] for similar ideas involving heavy flavor mesons and Ref. [168] for a supersymmetric realization). This enables very low reheating temperatures and is moreover directly testable by experiments such as CODEX-b, as well as Belle II.…”
Section: Baryogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…[66,67] for similar ideas involving heavy flavor mesons and Ref. [168] for a supersymmetric realization). This enables very low reheating temperatures and is moreover directly testable by experiments such as CODEX-b, as well as Belle II.…”
Section: Baryogenesismentioning
confidence: 99%
“…This scenario can arise e.g. in models that address the baryogenesis puzzle [66,67,[166][167][168], as described in Sect. 2.4.9.…”
Section: New Physics Reachmentioning
confidence: 99%
“…involving neutrons, and for searches beyond the SM, such as decays with heavy neutrinos, axion-like particles and other dark matter candidates (e.g. [10][11][12]). The benchmark measurements that should be feasible already with the currently available LHCb dataset could employ Cabibbo-favoured open-charm decays such as B 0 s → D − s pn.…”
Section: Resultsmentioning
confidence: 99%
“…involving neutrons, and for searches beyond the SM. One particular example of the processes beyond the SM that satisfy the above conditions is the model suggested in [10][11][12], where heavy invisible particle is accompanied by a SM baryon. As a benchmark SM decay mode, one can consider the decay B 0 s → D − s pn, which satisfies both conditions and should have a significant rate since it proceeds via the favoured b → c transition.…”
Section: Introductionmentioning
confidence: 99%
“…We showed by both analytic formulas and numerical calculations that the resulting theory (abbreviated as ISS-NMSSM hereafter) was one of the most economic framework to generate the neutrino mass and, meanwhile, to reconcile the DM DD experiments naturally [8,14]. We add that, besides us, a lot of authors have showed interest in the sneutrino DM in recent years [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], but none of them considered the same theoretical framework as ours.…”
Section: Introductionmentioning
confidence: 83%